PENGETAHUAN DAN SIKAP PERAWAT SAAT MEMBERIKAN EDUKASI RELAKSASI NAFAS DALAM SEBELUM PEMBEDAHAN - Rosalia Dewi Sekarini; Kristina Lisum (2020)
Education of deep breath relaxation techniques is a form of nursing intervention during the preparation stage of surgery This study aims to know the knowledge and attitude of nurses in providing education of deep breath relaxation techniques in pre-surgical patients. The method used in this study is quantitative method with cross sectional design. A sample of 59 nurses working in the adult surgical medical treatment room of RS X. Analysis using univariate, Kendall's tau b test. Results showed 40 (85.1%) nurses have good knowledge to educate deep breath relaxation techniques in pre-surgical patients, while those with knowledge are quite mostly not educating deep breath relaxation techniques in pre-surgical patients as many as 9 nurses (75%). Nurses who were positive to educate deep breath relaxation techniques in pre-surgical patients 32 nurses (84.2%), and negative attitudes of nurses who did not educate deep breath relaxation techniques in pre-surgical patients there were 11 (52.4%) nurse. The results of further analysis showed there is a relationship between the nurse's knowledge about deep breath relaxation techniques and the implementation of deep breath relaxation techniques education in pre-surgical patients P-value = 0.001 and there is a relationship of nurse attitude in providing deep breath relaxation techniques with the implementation of education of deep breath relaxation techniques in pre-surgical patients P-value = 0.012. Nurses as educators are advised to further improve the quality of health services in providing health education to preoperative patients on how to reduce pain intensity by using a non-pharmacological approach.